ANALISIS FASA KRISTALIN PADA TULANG SAPI TIMOR DENGAN VARIASI WAKTU DAN TEMPERATUR PEMANASAN DENGAN PENGUJIAN XRD - raymundus rheymon soko; Erich U. K. Maliwemu; Dominggus G. H. Adoe (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2025)
The aim of this research is to identify the crystalline phase of Timor cattle bone powder and characterize it using XRD (X-Ray Diffraction) testing. This research uses a method of analyzing the results of XRD (X-Ray Diffraction) of Timor beef bones with variations in heating time and temperature. After the beef bones have been ground, the sample is oven-treated for 1 and 2 hours at a temperature of 1000C, then 5 grams of the sample is taken for testing using XRD (X-Ray Diffraction). The research results show that a 1 hour time variation at a temperature of 100 0C has a purity level of 84.07% with a diameter of 32.81 mm, and a crystallinity of 85.1%. And a time variation of 2 hours at a temperature of 1000C has a purity level of 76.68% with a diameter of 31.97 nm, and a crystallinity of 98.0%.